2022
DOI: 10.1021/jacs.1c11920
|View full text |Cite
|
Sign up to set email alerts
|

Development of Photolenalidomide for Cellular Target Identification

Abstract: The thalidomide analogue lenalidomide (Len) is a clinical therapeutic that alters the substrate engagement of cereblon (CRBN), a substrate receptor for the CRL4 E3 ubiquitin ligase. Here, we report the development of photolenalidomide (pLen), a Len probe with a photoaffinity label and enrichment handle, designed for target identification by chemical proteomics. pLen preserves the substrate degradation profile, phenotypic antiproliferative and immunomodulatory properties of Len, and enhances interactions with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 50 publications
3
39
0
Order By: Relevance
“…To study the effect of lenalidomide on the eIF3 complex, we initially examined the protein associations of endogenous eIF3i after coimmunoprecipitation from HEK293T cells stably expressing CRBN (HEK293T-CRBN) with or without lenalidomide at 50 µM, 9 a concentration relevant to the anti-inflammatory and antiangiogenetic uses of lenalidomide. 18-20 Given the direct interactions of eIF3i with eIF3b and eIF3g elucidated in the cryo-EM and crystal structure of the eIF3 subcomplex (b:g:i) in the eIF3 complex, 14, 21, 22 we found that eIF3i coimmunoprecipitated with eIF3b and eIF3g, as expected ( Figure 1b ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To study the effect of lenalidomide on the eIF3 complex, we initially examined the protein associations of endogenous eIF3i after coimmunoprecipitation from HEK293T cells stably expressing CRBN (HEK293T-CRBN) with or without lenalidomide at 50 µM, 9 a concentration relevant to the anti-inflammatory and antiangiogenetic uses of lenalidomide. 18-20 Given the direct interactions of eIF3i with eIF3b and eIF3g elucidated in the cryo-EM and crystal structure of the eIF3 subcomplex (b:g:i) in the eIF3 complex, 14, 21, 22 we found that eIF3i coimmunoprecipitated with eIF3b and eIF3g, as expected ( Figure 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these data indicate that eIF3i is a direct target of CRBN and lenalidomide in MM.1S and MOLM13 cells, and that this interaction becomes observable when other targets such as IKZF1 are degraded ( Figure 5c ). Although the degradation of IKZF1 is almost complete at 8 h in both MM.1S and MOLM13 ( Figure S11, S13 ), 5-day incubation with lenalidomide was reported to be needed for antiproliferative effects in MM.1S and MOLM13, 2, 9, 30 which indicates that additional factors may contribute to the cytotoxicity of lenalidomide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A lenalidomide derivative bearing a diazirine photoaffinity handle was recently shown to label His353 in CRBN following UV irradiation, 47 through a mechanism that may involve nucleophilic attack of the imidazole residue on the diazo intermediate. 48 This study and ours reveal the surprisingly high reactivity of His353 in CRBN (a residue that is highly conserved across species) and we thus speculate that this may reflect its possible role in the endogenous function of CRBN.…”
Section: Discussionmentioning
confidence: 99%